HapticMaster - a generic force controlled robot for human interaction - van der Linde, R.Q.; Lammertse, P. (Industrial robot, 2003)
This paper describes the technical principles of a high-performance force controlled robot, called the HapticMaster. It is designed as a generic platform for applications with human interaction. Therefore, it differs significantly from most industrial robots on the one hand, whereas it also differs from most haptic interfaces on the other hand due to its power. An admittance control paradigm is used, which facilitates a high joint stiffness in combination with high force sensitivity. Typical applications for the HapticMaster are found in virtual reality, haptics research, and robot rehabilitation.